PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA DI SMA NEGERI 3 MEDAN - Nababan, Chindy Eskana; Siregar, Wildawani; Aisyah, Siti (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2025)
This research aims to examine whether using the Problem Based Learning (PBL) learning model can improve the activity and mathematics learning outcomes of class XI 3-2 students at SMA Negeri 3 Medan. This research uses Classroom Action Research (PTK). The respondents of this research were students of class Data collection was carried out by observing teacher activities in managing learning and student activities in the learning process, and learning results tests. This observation is used to determine the teacher's ability to manage learning and student activities in the learning process using the Problem Based Learning (PBL) learning model. Learning outcome tests are used to see student learning outcomes. The research results showed that teacher activity in cycle I was 80.77% (very good) then in cycle II 96.15% (very good). Meanwhile, student activity in cycle I was 70.83% (good) and in cycle II it was 91.67% (very good). Through the results of student research in cycle I and cycle II, it can be seen that there has been an increase in student activity after being given action through the Problem Based Learning (PBL) learning model. Meanwhile, students' classical learning outcomes in cycle I were 57.14% (Medium) with an average of 76.36 and in cycle II it was 88.57% (Very high) with an average of 87.71. The increase in learning outcome tests that occurred in cycle I and cycle II shows that the Problem Based Learning (PBL) learning model can improve student learning outcomes.